2022
DOI: 10.21203/rs.3.rs-2398051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in body mass index, weight, and waist-to-hip ratio over five years in HIV-positive individuals in the HIV Heart Aging Study compared to the general population

Abstract: Purpose: Overweight and obesity have increased in people living with HIV (PLH). Our study evaluated weight, body-mass-index (BMI), and waist-to-hip ratio (WHR) change over 5 years of follow-up in PLH compared to the general population. Methods: HIV-positive participants in the HIV Heart Aging (HIVH) study were matched 1:2 by age and sex with HIV-negative controls of the population-based Heinz Nixdorf Recall (HNR) study. Both studies were recruited in the German Ruhr area. The association between HIV and weig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Increasing age and higher BMI were the only risk factors independently associated with MetS similar to several other studies conducted in high and LMICs (26,27). In this study, the prevalence of MetS was also found to increase with age with the highest odds among those aged >50.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing age and higher BMI were the only risk factors independently associated with MetS similar to several other studies conducted in high and LMICs (26,27). In this study, the prevalence of MetS was also found to increase with age with the highest odds among those aged >50.…”
Section: Discussionsupporting
confidence: 90%
“…Although previous studies have evaluated the use of anthropometric indicators in the general population and in PLHIV 8, 14,21,[26][27][28][29][30][31][32][33] , no study has addressed a large number of anthropometric indicators at the same study in the HIV population and tested their association with cardiovascular risk. Thus, the objective of this study was to test the association of eleven anthropometric indicators with cardiovascular risk in PLHIV.…”
Section: Introductionmentioning
confidence: 99%